The role of Slovaks in the development of Sokolism in Stara Pazova: unity under the Slavic banner - Lapčević, Stevo (Napredak, 2026)
The author underlines the role which members of the Slovak Sokol from Stara Pazova had in the de velopment of Sokolism, and accordingly in strengthening Serbian-Slovak ties in Srem and Vojvodina. The Slovak Sokol was the first organisation of this kind established on the territory of Austria-Hungary. To this end, the author presents an overview of activities both of the Slovak Sokol organisation as well as Slovaks, members of the Stara Pazova Sokol Society, thereby particularly focusing mainly on joint Serbian-Slovak work on establishing this society and then on what soon followed, i.e., them joining the Yugoslav Sokol organisation and ultimately their building and development efforts which eventually resulted in constructing the Sokol House, a magnificent monument to the Serbs and Slovaks, volunteer soldiers in the Great War, and mounting a memorial plaque in honour of Tomáš Garrigue Masaryk and King Alexander Karađorđević. In this connection, the author also notes some potentially prospective directions for developing Serbian-Slovak cooperation through renewing if not the Sokol movement on its former foundation, then through reviving the spirit of mutual unity and personal endeavours for the greater good of community
Keywords: Serbs; Slovaks; Srem; Sokols; Masaryk; freedom; unity